Trends in alcohol-associated liver disease mortality rates in American Indians and Alaskan Natives - Yousaf Zafar; Isaac M. E. Dodd; Arsalan Zafar Iqbal; Laila Manzoor; Naveed Zafar Iqbal; Kristen D. Dodd; Jan Petrasek (BMC Public Health)
Abstract Introduction A leading cause of death among non-Hispanic American Indians or Alaskan Natives (AI/ANs), apart from cardiovascular disease and unintentional injuries, is chronic liver disease (CLD). This study analyzed recent trends in AI/AN ALD mortality, given their increased incidence of alcoholic liver disease (ALD) and high burden of CLD. Methods This cross-sectional study used data from the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER). Geographic, age and sex-based temporal mortality trends of ALD deaths were analyzed among the AI/AN population in the US from 1999 to 2020. Joinpoint regression analyses determined trends in ALD crude and age-adjusted mortality rates, identifying the annual percent change (APC) in each subgroup. Results In 1999–2020, the overall age-adjusted mortality rate (AAMR) among AI/ANs increased significantly from 27.2/100,000 to 88.4/100,000. Although men had a higher mortality rate overall, women had a higher increase in APC (2003–2008 APC was 17.7 [95% Cl: 9.9–26.0] and 2018–2020 APC was 25.3 [95% Cl: 11.4–40.9]) compared to men (1999–2020 APC was 5.8 [95% Cl 4.8–6.8]). All age groups studied witnessed an increase in AAMR. However, the age group 45–64 had the highest mortality overall in the preceding 2 decades. Non-metropolitan geographic regions had the highest mortality rate (2018–2020 APC of 25.5 [95% Cl: 5.0–50.0]) compared to medium/small or large metro areas. Western and Midwestern US Census regions had the highest mortality rates. Conclusions Male sex, age 44–65, and rural dwelling was associated with a greater ALD AAMR in AI/AN populations. Social changes due to the Covid-19 pandemic may have led to increased ALD mortality. Discerning the underlying causality of these associations and examining the impact of the social determinants of health, may represent important opportunities to enhance care for AI/ANs as a vulnerable minority population.